Study on the 2D Optimization Simulation of Complex Five-Hole Cutting Blasting under Different Lateral Pressure Coefficients. (10th June 2020) - Gao, Jing; Xie, Shizhen; Zhang, Xiantang; Wang, Hongli; Gao, Wenle; Zhou, Hongmin
Abstract : With the decrease and depletion of shallow coal resources, the depth of mining is increasing. The mechanism of high crustal stress blasting is not clear, and the effect of crustal stress on blasting effect is obvious. The law of the differential detonation is similar without crustal stress. The crustal stress of rock masses increases linearly with the increase in excavation depth, and the influence of crustal stress on blasting effect is great. In order to study the rock-breaking process of complex differential blasting under deep high crustal stress, the instantaneous detonation of each model and the priority detonation of the central hole are numerically simulated. The evolution law of the blasting crack and the method of optimizing blasting effect by differential blasting and increasing the aperture of the priority detonation hole under high crustal stress are put forward. The authors proposed a study on the 2D optimization simulation of complex five-hole cutting blasting under different lateral pressure coefficients of 400 m and 800 m with software ANSYS/LS-DYNA and analyzed the evolution rules of blasting cracks and lateral pressure coefficients. The results show that setting delayed detonation and hole diameter and optimizing blasthole spacing can optimize the rock-breaking effect under high crustal stress and different lateral pressure coefficients.